Interpretation of the Prohibition on Non-Muslim Leaders in the Qur’an (Fazlurrahman's Hermeneutical Perspective) - Adam Wildan Sholeh; Moch. Farich Alfani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The problem of non-Muslim leaders reaps many differences of opinion between figures and each other, they have strong arguments with each other to justify their arguments. One of those who contributed to this conversation was Prof. H. Nadirsyah Hosen, Ph.D or often called gus Nadir. He created a book with the title